Synthesis and Characterization of New Fused Heterocyclic Compounds Consisting of Benzodiazepine, Quinoxaline, Benzimidazole and Thiazole Rings (Baghdad Science Journal, 2025)
In this study, new heterocyclic compounds were synthesized through the cyclization reactions of o-phenylenediamine (1) with various organic reagents. Benzodiazepine derivatives (2-4) were obtained by reaction of (1) with ethylacetoacetate, malonic acid and acetyl acetone.Treatment of compound (1) with chloroacetamide, chloroacetic acid, p-bromophenacyl bromide and oxalic acid dihydrate afforded quinoxaline derivatives (5-8), respectively. Reaction of compound (1) with benzoic acid, piperonal, cyclohexanone and carbon disulfide resulted in the formation of compounds (9-12), respectively. Finally, reaction of compound (12) with chloroacetic acid in the presence of potassium hydroxide produced compound (13).